Hippocampal Injections of Oligomeric Amyloid β-peptide (1–42) Induce Selective Working Memory Deficits and Long-lasting Alterations of ERK Signaling Pathway - Faucher, Pierre; Mons, Nicole; Micheau, Jacques; Louis, Caroline; Beracochea, Daniel J. (Frontiers in Aging Neuroscience, 2016)
Increasing evidence suggests that abnormal brain accumulation of soluble rather than aggregated amyloid-β1-42 oligomers (Aβo(1-42)) plays a causal role in Alzheimer’s disease (AD). However, as yet, animal’s models of AD based on oligomeric amyloid-β1-42 injections in the brain have not investigated their long-lasting impacts on molecular and cognitive functions. In addition, the injections have been most often performed in ventricles, but not in the hippocampus, in spite of the fact that the hippocampus is importantly involved in memory processes and is strongly and precociously affected during the early stages of AD. Thus, in the present study, we investigated the long-lasting impacts of intra-hippocampal injections of oligomeric forms of Aβo(1-42) on working and spatial memory and on the related activation of ERK1/2. Indeed, the extracellular signal-regulated kinase (ERK) which is involved in memory function had been found to be activated by amyloid peptides. We found that repeated bilateral injections (1injection/day over 4 successive days) of oligomeric forms of Aβo(1-42) into the dorsal hippocampus lead to long-lasting impairments in two working memory tasks, these deficits being observed seven days after the last injection, while spatial memory remained unaffected. Moreover, the working memory deficits were correlated with sustained impairments of ERK1/2 activation in the medial prefrontal cortex and the septum, two brain areas tightly connected with the hippocampus and involved in working memory. Thus, our study is first to evidence that sub-chronic injections of oligomeric forms of Aβo(1-42) into the dorsal hippocampus produces the main sign of cognitive impairments corresponding to the early stages of AD, via long-lasting alterations of an ERK/MAPK pathway in an interconnected brain networks.